Analisis Miskonsepsi Hukum Newton pada Siswa Kelas XI MIA 1 di SMA Katolik Santo Andreas Palu - Maya Kristanti Landusa; Syamsu Syamsu; Muhammad Ali (Jurnal Kreatif Online, 2021)
The study aimed to find out the misconceptions of Newton's Law in class XI MIA 1 students at SMA Katolik Santo Andreas Palu. The data collection instrument was a multiple-choice test with a total of 15 questions regarding Newton's Law material accompanied by a Certainty of Response Index (CRI) test to determine the respondent's level of confidence in answering the questions. The test result data was analyzed to determine the percentage of misconceptions in each given question. The conclusion of this study is that the students of class XI MIA 1 at SMA Katolik Santo Andreas Palu experienced misconceptions which were included in the moderate category with an average percentage of 40.30%. Thus, it is necessary to pay attention to students in the form of providing examples of applications in everyday life, balancing teaching between concepts and calculations, giving explanations to students in accordance with existing concepts, asking back lessons that have been learned, and providing remediation.